An Overview of Systematic Review on Cupping Therapy: Case Study of Hypertension (Journal of Pharmaceutical Negative Results, 2022)
Efforts to reduce the prevalence of hypertension, several attempts have been undertaken, one of which is cupping therapy, both wet and dry cupping. Cupping was aimed to remove blood which brings about a detrimental effect on the body and eventually shows potential cause of harm from common symptoms to those which will likely decrease health. The aim of this article was to prove that cupping became an alternative in reducing the prevalence of hypertension. The method used was a systematic review by conducting several selections until 23 articles were selected. The results obtained from the selected articles were using wet cupping (12 articles), 9 articles for cupping and 1 article did both. Hijamah cupping therapy or wet cupping provides a great opportunity as a medical treatment for better blood pressure. Therefore, effective wet cupping will likely develop baroreceptor sensitivity for lower blood pressure for elderly patients of hypertension up to 4 weeks, without serious side effects. There are articles that use participants under the age of 20 years, this indicates that this hypertension has attacked at the ages before productive, namely under 20 years.